PROSPECTS OF ISLAMIC FINANCE IN THE KYRGYZ REPUBLIC: THE EXPERIENCE OF THE PERSIAN GULF COUNTRIES AND POLITICAL CHALLENGES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines the prospects for the development of Islamic finance in the Kyrgyz Republic, taking into account the experience of the Persian Gulf countries. The main instruments of Islamic banking — mudaraba, murabaha, ijara, takaful — and the possibilities of their adaptation in the financial and legal system of the Kyrgyz Republic are analyzed. Special attention is paid to the role of the National Bank, legislative restrictions, as well as political factors affecting the implementation of Islamic financial institutions. It is noted that the Gulf countries demonstrate the high efficiency of Islamic banking, integrating it with digital technologies and the ESG agenda, while Kyrgyzstan is at the stage of institutional formation. The key challenges are identified: the lack of specialized legislation, poor financial literacy of the population, and the need for political support. It is concluded that the development of Islamic finance can become a factor of economic diversification and a tool for strengthening cooperation between the Kyrgyz Republic and the countries of the Persian Gulf.
Keywords: Islamic finance, Kyrgyz Republic, Persian Gulf, Islamic banking, mudaraba, murabaha, political risks, economic integration.